Structure dynamics and solvation of HIV-1 protease wildtype complexed with inhibitors by molecular dynamic simulations - Kitiyaporn Wittayanarakul (Chulalongkorn University, 2014)
Thesis (Ph.D.)--Chulalongkorn University, 2006